Flurbiprofen 8.75 mg lozenges for treating sore throat symptoms: a randomized, double-blind, placebo-controlled study. (November 2016) - Schachtel, Bernard P; Shephard, Adrian; Shea, Timothy; Sanner, Kathleen; Savino, Laurie; Rezuke, Jeanne; Schachtel, Emily; Aspley, Sue
Aim: This study assessed multiple doses of flurbiprofen 8.75 mg lozenges for the relief of three prominent symptoms of acute pharyngitis: pain intensity (primary end point), difficulty swallowing and swollen throat.Patients & methods: A total of 204 patients (102 in each group) with confirmed pharyngitis (onset ≤4 days) were randomly assigned to take up to five flurbiprofen or placebo lozenges every 3–6 h, for 7 days. Using validated rating scales (sore throat pain intensity, difficulty swallowing and swollen throat) patients rated their symptoms for the duration of the study.Results: Over the first 24 h, patients treated with flurbiprofen lozenges reported significantly greater reductions in sore throat pain (47%) as well as difficulty swallowing (66%) and swollen throat (40%) compared with placebo (all p < 0.05).Conclusion: Multiple doses of flurbiprofen lozenges provide effective relief of sore throat pain intensity as well as difficulty swallowing and swollen throat.